PERAN DAKWAH DARING UNTUK MENJAGA SOLIDARITAS SOSIAL DI MASA PANDEMI COVID 19 - Setyowati Setyowati; Anggi Cahya (Academica : Journal of Multidisciplinary Studies, 2020)
The pandemic state demands the limitation of face-to-face social processes for spiritual needs through da'wah which is likely to be the intake for most of the Muslim community, especially in the IAIN Surakarta environment. This study analyzes da'wah which is carried out online which can be one of the performances to achieve social solidarity. Methods of data collection through interviews and observations. This research method is descriptive qualitative on phenomenology. The results of this study show that from the implementation of preaching KR and HM have adjusted their needs during the pandemic, namely by doing it online so that DE and FA can still study by optimizing social restrictions and implementing health protocols. This is a form of mutual concern which is an instrument of public compliance to build a sense of solidarity during a pandemic.Keywords:Â Social Solidarity; Dawah; Online; Pandemi